Complex and Unpredictable Consequences: Jewish Responses to the Catastrophe of 1096 - Muntean, Fritz (Pomegranate, 2000)
The long-term effects of these catastrophes derived less from the actual incidents themselves than from what was written about these events by the survivors, immediately afterwards and during the following generation.